Phubbing and Its Impact on Student Communication and Relationship: A Qualitative Study on Coping Strategies and Social Implications - Mawadah Rahmah; Sigit Sanyata (STAI Hubbulwathan Duri, 2024)
Phubbing—ignoring someone during interactions to focus on a smartphone—has emerged as a prevalent issue that negatively affects communication and interpersonal relationships, particularly among students. This study examines the impact of phubbing on students' relationships and explores coping strategies to mitigate its effects. A qualitative research approach was employed, involving in-depth interviews with five students from diverse academic and social backgrounds. The small sample size facilitated a detailed exploration of individual experiences and perspectives. Findings indicate that phubbing significantly harms interpersonal relationships by fostering feelings of disrespect, reducing attention, and undermining trust and intimacy. Participants reported experiencing frustration and diminished social interaction quality. Coping strategies identified include direct communication to address distractions, engaging in alternative activities, adapting behaviors to social contexts, and using humor to alleviate tension. The study highlights the detrimental effects of phubbing on student relationships and underscores the importance of addressing this behavior. Coping strategies identified offer practical tools for mitigating phubbing's impact, promoting healthier communication and stronger interpersonal bonds. Phubbing poses a substantial challenge to student relationships, necessitating greater awareness and proactive measures to improve communication and relational dynamics. Future initiatives should focus on educating students about the consequences of phubbing and fostering strategies to enhance relationship quality.